2009
DOI: 10.1037/a0015517
|View full text |Cite
|
Sign up to set email alerts
|

An experience sampling study of learning, affect, and the demands control support model.

Abstract: The demands control support model (R.A. Karasek & T. Theorell, 1990) indicates that job control and social support enable workers to engage in problem-solving. In turn, problem-solving is thought to influence learning and well-being (e.g, anxious affect, activated pleasant affect).Two samples (N = 78, N = 106) provided data up to four times per day for up to five working days. We assessed the extent to which job control was used for problem-solving by measuring the extent to which participants changed aspects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 79 publications
6
78
2
Order By: Relevance
“…Other forms of coping enacted by control and support, for instance avoidance and affective expression, were also found to be related to indicators of well-being and cognitive performance. In two samples, Daniels et al (2009) found some support for Karasek and Theorell"s active learning hypothesis of the DCSM (1990), in which learning is hypothesised to mediate the effects of job control and support enacted to solve problems on well-being. Consistent with de Jonge and Dormann (2006), the cognitive variable of learning was related to resources used for cognitive oriented coping (problem-solving) in response to a cognitive stressor (problem-solving demands).…”
Section: Coping and Matchmentioning
confidence: 92%
See 3 more Smart Citations
“…Other forms of coping enacted by control and support, for instance avoidance and affective expression, were also found to be related to indicators of well-being and cognitive performance. In two samples, Daniels et al (2009) found some support for Karasek and Theorell"s active learning hypothesis of the DCSM (1990), in which learning is hypothesised to mediate the effects of job control and support enacted to solve problems on well-being. Consistent with de Jonge and Dormann (2006), the cognitive variable of learning was related to resources used for cognitive oriented coping (problem-solving) in response to a cognitive stressor (problem-solving demands).…”
Section: Coping and Matchmentioning
confidence: 92%
“…The ideas here are that specific measures provide a better basis for uncovering the stress-buffering effects of job resources (Chrisopoulos et al, this volume;de Jonge & Dormann, 2006) or provide a better basis for examining how job resources facilitate specific forms of coping (Daniels, Boocock, Glover, Hartley & Holland, 2009;Daniels & Harris, 2005). In the following two sections, different approaches to specificity in match research will be described.…”
Section: Match and Person-environment Fitmentioning
confidence: 99%
See 2 more Smart Citations
“…Job crafting, which emphasizes the active role employees play in the design of their jobs by shaping the physical, emotional, relational, and/or cognitive aspects of their job tasks (Grant & Parker 2009, Wrzesniewski & Dutton 2001, may motivate learning. To meet their needs, individuals may job craft in a variety of ways, but through increasing structural job resources, social resources, and challenging job demands, individuals are likely to learn both informally, through social interactions, and formally, through participation in formal training and development programs (Daniels et al 2009, Tims & Bakker 2010). …”
Section: Work Environmentmentioning
confidence: 99%